The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2020
DOI: 10.1080/23802359.2020.1756955
|View full text |Cite
|
Sign up to set email alerts
|

The complete plastid genome sequence of Quercus ciliaris (Fagaceae)

Abstract: Quercus ciliaris C.C.Huang & Y.T.Chang is one of the dominant tree species in the subtropical evergreen broad-leaved forests of China. In this study, we sequenced and analyzed the complete chloroplast (cp) genome of the species. The circular genome is 160,842 bp in size, consisting of two copies of inverted repeat (IR) regions of 25,823 bp, one large single-copy (LSC) region of 90,294 bp, and one small singlecopy (SSC) region of 18,902 bp. It encodes a total of 114 unique genes, including 80 protein-coding gen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
2
1

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 5 publications
0
3
0
Order By: Relevance
“…With the rapid development of next-generation sequencing, cp genomes are increasingly being used for phylogenetic relationship reconstruction (Li et al 2020a;Mu et al 2020;Zhao et al 2020;Uckele et al 2021). Since the first oak cp genome for Q. rubra was published in 2014, up to 30 species have been sequenced (Alexander & Woeste 2014;Li et al 2020b;Zhang et al 2020). Although angiosperm cp genomes exhibit a remarkably conserved gene content and order (Jansen & Ruhlman 2012), complete cp genome data will provide more valuable information for understanding the phylogenetic relationships and intraspecific diversity of Quercus (Li et al 2018).…”
Section: Introductionmentioning
confidence: 99%
“…With the rapid development of next-generation sequencing, cp genomes are increasingly being used for phylogenetic relationship reconstruction (Li et al 2020a;Mu et al 2020;Zhao et al 2020;Uckele et al 2021). Since the first oak cp genome for Q. rubra was published in 2014, up to 30 species have been sequenced (Alexander & Woeste 2014;Li et al 2020b;Zhang et al 2020). Although angiosperm cp genomes exhibit a remarkably conserved gene content and order (Jansen & Ruhlman 2012), complete cp genome data will provide more valuable information for understanding the phylogenetic relationships and intraspecific diversity of Quercus (Li et al 2018).…”
Section: Introductionmentioning
confidence: 99%
“…A total of 131 genes, including 86 PCGs, 37 tRNAs and 8 rRNA genes, were annotated in the chloroplast genomes of 50 species (Tables 1 and 2). Previous studies of the chloroplast genome sequences downloaded from NCBI database have found that using different annotation software and reference genome sequences can lead to differences in the annotation results [74][75][76]. The ycf15 gene is de ned as a pseudogene because it does not encode proteins; therefore, it is not annotated in most chloroplast genomes of Quercus.…”
Section: Discussionmentioning
confidence: 99%
“…Phylogenetic analyses were conducted using 53 cp genome sequences belonging to six white oaks (section Quercus) [66][67][68][69], three Cerris oaks (section Cerris) [68,[70][71][72][73], six ringcupped oaks (section Cyclobalanopsis) [74][75][76][77][78][79], 11 Ilex oaks (section Ilex) [67][68][69]71,[80][81][82][83], and two outgroups in Fagus [78,84] (Table S2). The HomBlocks v.1.0 pipeline [85] was applied to identify shared locally collinear blocks and generate a phylogenetically informative matrix of 83,130 bp.…”
Section: Phylogenetic Analyses Of Chloroplast Genome Sequencesmentioning
confidence: 99%